Grundsätzliches zum Unterschied zwischen tropischem und außertropischem Gletscherhaushalt unter besonderer Berücksichtigung der Gletscher Boliviens - Jordan, Ekkehard (ERDKUNDE, 1979)
Knowledge of mass economies of tropical glaciers is still very inadequate. Although tropical glaciers cover only 2000-3000 km², thus amounting to only about 1 per cent of theentire montane glaciation, 95 per cent of them are situated in the periodically-humid tropics, and take on the important function of water supply during the dry season. As a result of insufficient precipitation there is transition from the almost perennially-fed glaciers to the complete absence of glaciation in Bolivia, which, with a glacial area of almost 1000 km², belongs to this marginally tropical type. The distribution of glaciers in Bolivia in their dependence on relief and climate is presented, and the totally different character of the tropical-marginally tropical glacier mass economy derived from the temporal regime of the climate as well as the observations and measurements carried out in 1975 and 1977. The difference from the glaciers of higher latitudes is chiefly to be seen in the absence of a strict annual periodicity, which renders the usage of the natural annual economy absolutely impossible. More exact quantitative proofs can only be achieved on the basis of a series of measurements extending over several years